Perempuan dan Pendidikan: Studi Historis-Kritis Dari Zaman Klasik Hingga Modern Dalam Konteks Pendidikan Islam - Listi Hani Siregar; Siti Juraida Hasibuan; Abdusima Nasution (Albayan Journal of Islam and Muslim Societies, 2025)
This article critically examines the position and role of women in education through a historical and Islamic perspective. The discussion traces the development of women’s education from ancient civilizations, the pre-Islamic era, the classical Islamic period, to the modern and contemporary context. Using a qualitative library research method with a historical-critical approach, this study analyzes normative Islamic texts, historical records, and contemporary scholarly works to explore the gap between Islamic ideals and social practices regarding women’s education. The findings demonstrate that women’s education has strong theological legitimacy in Islam and has played a significant role in the transmission of knowledge and the development of civilization. Furthermore, the emergence of women-only educational institutions reflects adaptive strategies to expand access while responding to socio-cultural contexts. This study argues that strengthening women’s education is not merely a matter of gender equality, but a strategic foundation for building an ethical, knowledgeable, and sustainable society.